Automated transportation systems subject to interruptions in production and intralogistics - a survey and evaluation. Issue 4 (2018) - Wior, Ireneus; Jerenz, Stefan; Fay, Alexander
To increase efficiency and productivity of production and intralogistic facilities, automated transportation systems are widely used nowadays. This paper examines effects of interruptions in different transportation systems on the performance of production and intralogistic facilities by evaluating current literature with a focus on simulation-based studies. Our first contribution is a new categorisation of conveyor-based and vehicle-based transportation systems. This categorisation does not follow a technological differentiation but focuses on the abilities of the transportation system categories to deal with transportation system interruptions. Thereafter, current literature in the domains of 'manufacturing systems', 'semiconductor facilities', 'general intralogistics' (e.g., warehouses), and 'container terminals' is surveyed with respect to this categorisation. This survey is our second contribution and aims to identify research directions thus far not sufficiently considered. Finally, having surveyed different domains, the strengths and weaknesses of different transportation system categories are extracted from the literature and summarised. That summary is our final contribution, and is intended as a guideline and support for engineers planning transportation systems. Two main shortcomings in the current literature are identified: Firstly, although recognised as significantly influencing the facility's performance, transportation interruptions are not sufficiently considered. Secondly, relatively few simulation studies compare different categories of transportation systems.